(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the problem of developing transmedia competence in journalism education in the context of globalization. The authors analyze the theoretical and practical aspects of this concept and its advantages in communicating with an audience. They emphasize the importance of combining theoretical knowledge, practical skills, technical literacy, and students’ creative thinking. Thus, training competitive and globally minded professionals is defined as the primary goal of the educational process.